Evidence of poro-elastic inflation at the onset of the 2021 Vulcano Island (Italy) unrest - Stissi, Santina Chiara; Currenti, Gilda; Cannavò, Flavio; Napoli, Rosalba (Frontiers in Earth Science, 2023)
Thermal and pore-pressure variations induced by the circulation of hydrothermal fluids in porous and permeable media contribute to ground deformation in volcanic areas. In this paper, we use solutions for the calculation of the displacements induced by pore-pressure and temperature changes for simplified geometry sources embedded in an elastic half-space with homogeneous mechanical and porous properties. The analytical solution for a spherical source is reviewed and a semi-analytical approach for the calculation of the displacement for a cylindrical source is presented. Both models were used for the inversion of the daily deformation data recorded on Vulcano Island during the 2021 unrest. Starting from September 2021, Vulcano Island experienced a period of increases in gas emission, seismic activity and edifice inflation. The deformation pattern evolution from September until mid-October 2021 is indicative of a spatially stationary source. The modelling of the persistent and continuous edifice inflation suggests a deformation source, located below La Fossa crater at a depth of about 800 m from the ground surface undergoing a volume change of about 10 5 m 3 , linked to the hydrothermal system. The modelling results reveal that thermo-poro-elastic processes are sufficient to explain the observed displacement without necessarly invoking the input of new magma from depth. Our findings demonstrate that thermo-poro-elastic solutions may help in interpreting ground deformation and in giving insights into the evolution of the hydrothermal systems, providing useful implications for hazard assessment during volcanic crises.